Naming Buildings in Universities Based on the Names of National Figures to Ignite the Fighting Spirit of the Academic Community - Hasyim, Nur; Nurjanah, Darul (KnE Social Sciences, 2024)
The naming of the building at Universitas “X” as one of the leading universities in Indonesia is not fully known. This study investigates the reasons for naming places using the names of national figures, the language unit structure of place names, and the names of places that have been given special names. This qualitative research data were collected using a documentation study, a search for news on the internet with reliable sources of information, interviews with informants who have information about the building names at Universitas “X”, and direct observations. The data were analyzed qualitatively according to those presented by Miles dan Huberman: data reduction, display, and conclusion drawing. The research results in naming buildings based on the names of national figures intended so that the academic community can emulate national figures’ spirit, achievements, and fighting power. The phrase structure of building names based on the rules for English language toponymy is a combination of common nouns and proper nouns, such as Gedung Prof. Mr. H. Mohammad Yamin, Gedung Prof. Dr. Ace Partadiredja, and Gedung K.H. A. Wahid Hasyim. As a follow-up to this research, it can be investigated, among others, how to name streets or name rooms on campus with this Islamic spirit. Keywords: toponymy, place name, building name, universitas “X”